Evaluation of the Effect of Fixation Angle between Polyaxial Pedicle Screw Head and Rod on the Failure of Screw-Rod Connection - Engin Çetin; Mustafa Özkaya; Ümit Özgür Güler; Emre Acaroğlu; Teyfik Demir (Applied Bionics and Biomechanics)
Introduction. Polyaxial screws had been only tested according to the ASTM standards (when they were perpendicularly positioned to the rod). In this study, effects of the pedicle screws angled fixation to the rod on the mechanical properties of fixation were investigated. Materials and Method. 30 vertically fixed screws and 30 screws fixed with angle were used in the study. Screws were used in three different diameters which were 6.5 mm, 7.0 mm, and 7.5 mm, in equal numbers. Axial pull-out and flexion moment tests were performed. Test results compared with each other using appropriate statistical methods. Results. In pull-out test, vertically fixed screws, in 6.5 mm and 7.0 mm diameter, had significantly higher maximum load values than angled fixed screws with the same diameters (P<0.01). Additionally, vertically fixed screws, in all diameters, had significantly greater stiffness according to corresponding size fixed with angle (P<0.005). Conclusion. Fixing the pedicle screw to the rod with angle significantly decreased the pull-out stiffness in all diameters. Similarly, pedicle screw instrumentation fixed with angle decreased the minimum sagittal angle between the rod and the screw in all diameters for flexion moment test but the differences were not significant.